1994
DOI: 10.1007/bf02102644
|View full text |Cite
|
Sign up to set email alerts
|

Charge deficiency, charge transport and comparison of dimensions

Abstract: Abstract. We study the relative index of two orthogonal infinite dimensional projections which, in the finite dimensional case, is the difference in their dimensions. We relate the relative index to the Fredholm index of appropriate operators, discuss its basic properties, and obtain various formulas for it. We apply the relative index to counting the change in the number of electrons below the Fermi energy of certain quantum systems and interpret it as the charge deficiency. We study the relation of the charg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
289
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(292 citation statements)
references
References 40 publications
3
289
0
Order By: Relevance
“…The hallmark of localization is rapid (even exponential) decay of G E (x, y) at energies in the spectrum, though in this case it occurs with pre-factors which are not uniform in space and diverge at a dense countable set of eigenvalues. Rapid decay of the Green function is related to the non-spreading of wave packets supported in the corresponding energy regimes and various other manifestations of localization whose physical implications have been extensively studied in regards to the conductive properties of metals [8,55,73,1,54] and in particular to the quantum Hall effect [36,57,10,12,3].…”
mentioning
confidence: 99%
“…The hallmark of localization is rapid (even exponential) decay of G E (x, y) at energies in the spectrum, though in this case it occurs with pre-factors which are not uniform in space and diverge at a dense countable set of eigenvalues. Rapid decay of the Green function is related to the non-spreading of wave packets supported in the corresponding energy regimes and various other manifestations of localization whose physical implications have been extensively studied in regards to the conductive properties of metals [8,55,73,1,54] and in particular to the quantum Hall effect [36,57,10,12,3].…”
mentioning
confidence: 99%
“…Simon (1994a), avoiding the language of non-commutative geometry completely. Note that the operator U de ned by m ultiplication with u := X 1 + iX 2 jX 1 + iX 2 j (14) is the gauge transformation related to unit ux tube piercing the IR 2 at the origin.…”
Section: The Laughlin Argumentmentioning
confidence: 99%
“…We consider now an application of the index approach t o a quantum Hall system, following J. E. Avron, R. Seiler, B. Simon (1994a). Our model describes non relativistic, non interacting fermions in the punctured plane C n f a g , a 2 C, with random impurities.…”
Section: Index Approach To the Qhementioning
confidence: 99%
“…Later theoretical investigations showed that a topological phenomenon underlies this quantization: the integer n in the above formula was shown to be the first Chern number of a vector bundle, naturally associated to the quantum system [27,1,2]. The only role played by the magnetic field in quantum Hall systems is that of breaking time-reversal symmetry: if the system were time-reversal symmetric, then the Hall conductivity would vanish, and the system would remain in an insulating state.…”
Section: Introductionmentioning
confidence: 99%